2014
DOI: 10.7314/apjcp.2014.15.2.703
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Sequential Transcatheter Arterial Chemoembolization and Portal Vein Embolization prior to Major Hepatectomy for Patients with HCC

Abstract: Objective: To evaluate the safety and efficacy of sequential transcatheter arterial chemoembolization (TACE )and portal vein embolization (PVE) before major hepatectomy for patients with hepatocellur carcinoma (HCC). Methods: In this retrospective case-control study, data were collected from patients who underwent sequential TACE and PVE prior to major hemihepactectomy. Liver volumes were measured by computed tomography volumetry before TACE, and preoperation to assess degree of future remnant liver (FRL) hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Improvement in liver function by biliary drainage may provide symptomatic relief and allow for antitumor therapies, including transhepatic chemoembolization (TACE) and chemotherapy (Cui et al, 2012;Li et al, 2012;Mao et al, 2012;Kong et al, 2012;Xiong et al, 1 2012; Ma et al, 2013;Wang et al, 2013;Wang et al, 2013;Jong et al, 2013;Xu et al, 2014). Percutaneous Transhepatic Catheter Drainage (pTCD)/ Percutaneous Transhepatic Biliary Stengting (pTBS) is a method of biliary tree decompression, applied as palliative treatment in patients with inoperable malignant biliary obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Improvement in liver function by biliary drainage may provide symptomatic relief and allow for antitumor therapies, including transhepatic chemoembolization (TACE) and chemotherapy (Cui et al, 2012;Li et al, 2012;Mao et al, 2012;Kong et al, 2012;Xiong et al, 1 2012; Ma et al, 2013;Wang et al, 2013;Wang et al, 2013;Jong et al, 2013;Xu et al, 2014). Percutaneous Transhepatic Catheter Drainage (pTCD)/ Percutaneous Transhepatic Biliary Stengting (pTBS) is a method of biliary tree decompression, applied as palliative treatment in patients with inoperable malignant biliary obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…One study found that the FLR after sequential TACE and PVE increased from 32.3% to 71.4% (mean 55.4%). In addition, no patients had intra- or extrahepatic metastasis[19]. A Korean study compared the prognostic impact of preoperative sequential TACE and PVE or PVE alone in patients who underwent right liver resection for solitary HCC [7].…”
Section: Discussionmentioning
confidence: 99%
“…The most important factors in choosing optical stratery for TACE are to obtain favorable therapeutic effects and to reduce adverse side-effects (Xu et al, 2014). With regard to the embolic agent used in TACE for HCC, several studies have analyzed the efficacy of lipiodol (Idee and Guiu, 2013;Peng et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Transcatheter arterial chemoembolization (TACE) is an accepted treatment option for unresectable hepatocellular carcinoma (HCC) (Peng et al, 2014;Xu et al, 2014), of which equential TACE could an effective method to improve resection opportunity, expand the scope of surgical resection, as well as to greatly reduce postoperative intra-and extrahepatic metastasis (Xu et al, 2014). However, the long-term effectiveness of TACE remains limited.…”
Section: Discussionmentioning
confidence: 99%